Validation of data from an artificial sniffer dog by common analytical techniques - Hardy, Iona; Jakobsen, Mogens Havsteen; Treiberg, Tuule; Gotfredsen, Charlotte Held; Dossi, Eleftheria (SETCOR, 2021)
CRIM-TRACK, an artificial sniffer dog, employs a colourimetric sensor system to monitor the colour change of chromic dyes when in contact with the vapours of illicit molecules (analytes) for detection and identification of substances. Within, the interaction of illicit chemicals and chromic dyes have been studied in solution using Proton Nuclear Magnetic Resonance (1 H NMR) spectroscopy and Ultraviolet-Visible (UV-Vis) spectrophotometry, to validate data generated from detection experiments using CRIM-TRACK sniffer. 1 H-NMR revealed the colour change mechanism induced by benzyl methyl ketone (BMK), a precursor chemical of methamphetamines, was hydrogen bonding between the BMK and specific dye molecules. It also revealed that hexamine (HEX), an explosives precursor, induced a colour change by formation of ion pairs with the specific dye molecules. The colour changes detected by CRIM-TRACK were confirmed by UV-Vis where a shift in absorption wavelength and/or a change in absorbance occurred.
Keywords: chemical precursors; detection; colourimetric sensor; CRIM-TRACK sniffer system; NMR; UV-Vis